INNOVATIVE APPROACHES OF LANGUAGE TEACHING IN THE CONTEXT OF GLOBALIZATION - Navbahor Nasullayeva; Sabina Ibrohimova (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article examines innovative approaches to language teaching in the context of globalization, emphasizing the shift from traditional teacher-centered methods to more interactive, learner-centered practices. It highlights how globalization demands higher communicative competence and intercultural awareness, which modern methodologies aim to develop. The study explores several key approaches, including intercultural communication, data-driven learning (DDL), content-based learning (CBL), collaborative learning (CLL), personalized learning, and technology-enhanced language learning. Each approach is described in terms of its core principles, benefits, and potential limitations, supported by relevant examples from educational practice. The article also analyzes how these methods contribute to improving learners’ motivation, autonomy, and practical language use in real-life situations. The findings suggest that innovative approaches not only increase the effectiveness of language acquisition but also make the learning process more engaging, flexible, and relevant to global demands. Ultimately, integrating such methods is essential for preparing learners to successfully communicate and function in an increasingly interconnected world.